Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1016/s0002-9440(10)63275-0
|View full text |Cite
|
Sign up to set email alerts
|

TRIO Amplification and Abundant mRNA Expression Is Associated with Invasive Tumor Growth and Rapid Tumor Cell Proliferation in Urinary Bladder Cancer

Abstract: Studies by comparative genome hybridization have suggested that 5p amplification is related to tumor progression in urinary bladder cancer. In this study seven genes (TAS2R, ADCY2, DNAH5, CTNND2, TRIO, ANKH, and MYO10) located to 5p15.31-5p15.1 were analyzed by fluorescence in situ hybridization using a tissue microarray containing samples from tumors and cell lines with known 5p amplification by comparative genome hybridization. Amplification frequency was highest for TRIO, which maps to 5p15.2 and encodes a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 29 publications
(30 reference statements)
4
43
0
1
Order By: Relevance
“…FISH analysis confirmed that gain of 5p15.33 was not only associated with high histological grade but also advanced pathological stage. These observations are comparable with published data on bladder cancer obtained by conventional and array CGH analyses [3, 5, 9, 23]. In this study, we analyzed copy number gains, but not copy number loss.…”
Section: Discussionsupporting
confidence: 91%
“…FISH analysis confirmed that gain of 5p15.33 was not only associated with high histological grade but also advanced pathological stage. These observations are comparable with published data on bladder cancer obtained by conventional and array CGH analyses [3, 5, 9, 23]. In this study, we analyzed copy number gains, but not copy number loss.…”
Section: Discussionsupporting
confidence: 91%
“…TRIO contains three functional domains-a serine/threonine kinase domain and two guanine exchange factor domains. TRIO amplification and abundant expression was recently reported in lung carcinoma and bladder cancer (17)(18)(19). Although 5p amplifications have been well -documented in oral cancer, this is the first report of the microamplification of the TRIO locus in oral cancer, probably due to insufficient resolution of both conventional techniques and interval marker array CGH.…”
Section: Resultsmentioning
confidence: 76%
“…Located in this region, TRIO has previously been demonstrated to be amplified and overexpressed in bladder cancer and this was associated with the invasive phenotype, high grade and rapid proliferation, but not with progression. 41 We could not confirm overexpression of TRIO in our geneexpression microarray material. Although 5p-gains were associated with CIS, it was never the only chromosomal change in any sample.…”
Section: Discussionmentioning
confidence: 83%